Telesupervision Benefits for Placements: Allied Health Students’ and Supervisors’ Perceptions - Nagarajan, Srivalli; McAllister, Lindy; McFarlane, LuAnne; Hall, Mark; Schmitz, Corilie; Roots, Robin; Drynan, Donna; Avery, Lisa; Murphy, Sue; Lam, Mary (International Journal of Practice-based Learning in Health and Social Care, 2016)
Telesupervision (TS) uses Information and Communication Technology (ICT) for communication between university-based staff, clinical supervisors and students undertaking placements in the presence or absence of a clinical supervisor onsite. Despite examples of successful implementation (Carlin 2012, Chipchase et al. 2014, Dudding and Justice 2004, Hall 2013) there has been minimal uptake of TS in allied health. This study investigated students’ and clinical educators’ perceptions of the potential benefits and barriers of TS using readily accessible ICT during placements. During 2014-2015, telesupervision/telesupport was provided to a total of 54 Undergraduate and Graduate Entry Masters students from Speech Language Pathology (SLP), Occupational therapy (OT) and Physical therapy (PT) programs at one Australian and two Canadian universities and Exercise Physiology (EP) students at the Australian university. After receipt of TS, 39 students completed an online survey. Nine participating university-based clinical education coordinators (CECs) were interviewed about their experiences. Survey data were analysed using descriptive statistics and interview data were analysed using thematic analysis. Students valued regular TS contact/communication with their CEC to discuss challenges that arose during their placements. CECs believed students benefitted from the opportunities to discuss their placement experiences through TS sessions used for direct supervision and/or for complementing onsite supervision. Students used TS sessions to debrief and reflect on their placement experiences. CECs gained a better understanding of the students’ placement experiences. TS has the potential to develop greater connection between students and CECs and enhance student and supervisor experience of clinical education.